2012
DOI: 10.5152/balkanmedj.2012.050
|View full text |Cite
|
Sign up to set email alerts
|

Are Hepatic Portal Venous System Components Distributed Equally in the Liver? A Multidetector Computerized Tomography Study

Abstract: Objective: We aimed to evaluate the relationships between the splenic index, right and left hepatic lobe volumes, diameters of splenic vein (SV), superior mesenteric vein (SMV) and the portal vein (PV) by Multidetector Computerized Tomography (MDCT). We also investigated indirect signs of portal venous flow pattern using these parameters.Material and Methods: Following their contrast thoracoabdominal and abdominal 64-MDCT examinations, the images of 100 cases (61 males and 39 females) were evaluated retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As a human study, Moore and Bridenbaugh [ 7 ] performed portal venography and suggested that streamline flow exists, based on the finding that the SV flows mainly into the left lobe of the liver, whereas the SMV flows mainly into the right. In 2012, a study calculating the diameters of the main venous structures also suggested the existence of streamline flow [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a human study, Moore and Bridenbaugh [ 7 ] performed portal venography and suggested that streamline flow exists, based on the finding that the SV flows mainly into the left lobe of the liver, whereas the SMV flows mainly into the right. In 2012, a study calculating the diameters of the main venous structures also suggested the existence of streamline flow [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common route of bacterial seeding to the liver is hematogenous spread via the portal circulation. The right lobe in particular is involved in 72% of hepatic abscesses [ 6 ] as it receives the majority of portal circulation [ 9 , 10 ]. The intestinal microorganisms are able to cross the gut-vascular barrier and enter the venous circulation either via various virulence factors [ 11 ], or via intestinal perforations [ 12 ] similar to those caused by diverticulitis.…”
Section: Discussionmentioning
confidence: 99%
“…SpV blood flow is seen to uniformly opacify the MPV, which is in line with studies suggesting equal distribution of SpV blood between the right and left lobes. However, SMV flow is streamlined within the MPV in keeping with its preferential flow into the right lobe in many patients (Figure 2A) (11,23,35).…”
Section: Cbct Evaluation Of Individual Drainage Systemsmentioning
confidence: 99%